The equations of given lines are

x cos θ – y sin θ = k cos 2θ …………………… (1)

x sec θ + y cosec θ = k ……………….… (2)

Perpendicular distance (d) of a line Ax + By + C = 0 from a point (x_{1}, y_{1}) is given by

Compare equation (1) to the general equation of line that is., Ax + By +C = 0 ,

We get A = cos**θ** , B= -sin**θ** , and C = -k cos2**θ**

It is given that p is the length of the perpendicular from (0,0) to line (1).

\( q=\dfrac{|A(0)+B(0)+C|}{\sqrt{A^2+B^2}}\)

= \( q=\dfrac{|C|}{\sqrt{A^2+B^2}}\)

= \( q=\dfrac{|-k\;cos2θ|}{\sqrt{cos^2θ+sin^2θ}}\)

= \(| -k\;cos2θ|\) ..........(3)

Compare equation (1) to the general equation of line that is., Ax + By +C = 0 ,

We get A = sec**θ** , B= cosec**θ** , and C = -k

It is given that q is the length of the perpendicular from (0,0) to line (2).

\( q=\dfrac{|A(0)+B(0)+C|}{\sqrt{A^2+B^2}}\)

= \( q=\dfrac{|C|}{\sqrt{A^2+B^2}}\)

= \( q=\dfrac{|-k|}{\sqrt{sec^2θ+cosec^2θ}}\).............(4)

From (3) and (4) , we have

\( p^2+4q^2=(|-kcos2θ|)^2\)

\( +4 (\dfrac{|-k|}{\sqrt{sec^2θ+cosec^2θ}})^2\)

= \( k^2cos^22θ+(\dfrac{4k^2}{{sec^2θ+cosec^2θ}})\)

q = k cos θ sin θ

Multiply both sides by 2, we get

2q = 2k cos θ sin θ = k × 2sin θ cos θ

2q = k sin 2θ

Squaring both sides, we get

4q^{2} = k^{2} sin^{2}2θ …………………(4)

Now add (3) and (4) we get

p^{2} + 4q^{2} = k^{2} cos^{2} 2θ + k^{2} sin^{2} 2θ

p^{2} + 4q^{2} = k^{2} (cos^{2} 2θ + sin^{2} 2θ) [Since, cos^{2} 2θ + sin^{2} 2θ = 1]

p^{2} + 4q^{2} = k^{2}

Hence proved.

Answered by Pragya Singh | 1 year agoFind the angle between the line joining the points (2, 0), (0, 3) and the line x + y = 1.

Prove that the points (2, -1), (0, 2), (2, 3) and (4, 0) are the coordinates of the vertices of a parallelogram and find the angle between its diagonals.

Find the acute angle between the lines 2x – y + 3 = 0 and x + y + 2 = 0.

Find the angles between pairs of straight lines 3x – y + 5 = 0 and x – 3y + 1 = 0

Find the angles between pairs of straight lines 3x + y + 12 = 0 and x + 2y – 1 = 0